A Data mining model for Customer Relationship Management -A Review (International Journal of Engineering and Computer Science, 2015)
Data Mining is an analytic process designed to explore data in search of consistent patterns and/or systematic relationships between variables, and then to validate the findings by applying the detected patterns to new subsets of data. Data mining is challenging area and its possible applications in business provides an emerging research topic. It is about analyzing data patterns to extract knowledge for optimizing the customer relationships.